Quantifying industrial strategies across nine OECD countries - Criscuolo, Chiara (OECD Publishing, 2023)
Industrial policy has resurfaced prominently in academic and policy discussions in the wake of major shocks and long-term trends. However, quantifying industrial strategies across countries remains difficult. The 'Quantifying Industrial Strategies' (QuIS) project measures industrial policy expenditures by gathering and harmonising publicly available data, based on a new methodology. This report summarises the composition of industrial strategies in the first nine participating countries in terms of expenditures, priorities, and policy instruments for the period 2019-21. The report finds that industrial policies are sizeable, with 1.5% of GDP in grants and tax expenditures, and with an important heterogeneity across countries in terms of strategic priorities; industrial strategies mainly rely on sectoral instruments, representing on average 29% of grants and tax expenditures; and green instruments are important and rose significantly in six out of nine countries between 2019 and 2021
Keywords: Science and Technology; Economics; Industry and Services